The Effectiveness of Tepid Water Spong Intervention on Dengue Haemorrhagic Fever with Hyperthermi Nursing Problems in The Aster Room dr. Soebandi General Hospital Jember - Sufyan Asasi, Muhammad; Perdani Juliningrum, Peni; Rahmawati, Ira; Inganah (D'Nursing and Health Journal (DNHJ), 2024)
Introduction: Hyperthermia is an infection or inflammation caused by bacteria, viruses or other pathogens that stimulates the release of pyrogens that act in the hypothalamus, where they trigger the production of prostaglandins and increase the reference value (set point) of body temperature. Method: Data was collected using the observation method which was recorded in an observation sheet. The results showed that after giving tepid water sponge therapy for 3 days, the patient experienced a reduction in fever. Result: Implementation done in cases of dengue fever with hyperthermia is Hypertermia Management, which includes monitoring body temperature, providing a cool environment, loosening or unloading clothes, wet and soaking body surfaces, giving oral fluids, encouraging sleeping, and giving intravenous fluids and electrolytes. The second implementation that can be done is Temperature Regulation, which includes monitoring a child's body temperature every two hours, monitoring skin color and temperature, monitor blood pressure, respiratory frequency and pulse rate, increasing adequate fluid and nutritional intake, and providing antipyretics. Conclusion: The implementation process of nurses that have been given to patient with hypertermal problems in dengue haemorrhagic fever lasted for 3 days shift time with 3 times administration of therapeutic intervention tepid water Spong. Results of the nursery evaluation in patient. with the problem of hypertermia in Dengue Haemorhagic Fever in there is a decrease in the body temperature in the patient.